Abordagens funcionais e recursos terapêuticos na fisioterapia hospitalar: um estudo observacional retrospectivo - Garcia, Thais Guedes (Universidade Federal de São Carlos)
Physiotherapy plays a significant role and has a significant presence in the hospital environment, mainly by preventing complications from immobility and promoting improvements in functional and respiratory conditions, which can impact patients' length of stay. Therefore, understanding the resources used in the assessment and provision of hospital physiotherapy, as well as analyzing kinetic-functional data and length of stay, allows for obtaining detailed information about these practices and their impacts, in addition to supporting reflections aimed at potential improvements in institutional processes. Objective: To conduct a survey of the main assessment instruments, techniques, and physiotherapy resources used in different hospital inpatient units. Methods: This is a descriptive, retrospective study of medical record analysis, which sought to provide a detailed analysis of the physiotherapy care offered to patients hospitalized in wards and intensive care units. This analysis was conducted in the context of the University Hospital of UFSCar. The research encompassed a wide age range, including elderly and adults, reflecting the diversity of patients receiving physiotherapy care. Access to medical records was through the AGHUX electronic hospital record system. Clinical and hospitalization data from patients were collected, as well as data related to physiotherapy care, such as: which assessment instruments and intervention resources were most used, whether a physiotherapy diagnosis was established, whether the objectives and goals of physiotherapy care were clear, as well as patterns and content presented in the progress notes. Results: After data analysis, the most prevalent physiotherapy techniques and resources were found to be bedside sitting (77%), secretion removal therapy (47%), standing (64%), stretching (55%), and functional positioning (42%). The most evaluated aspects and instruments used by physiotherapists were respiratory rate, peripheral oxygen saturation, pulmonary auscultation, heart rate, Glasgow Coma Scale, and ICU Mobility Scale (IMS). The physiotherapeutic diagnosis was established in 4.7% of the consultations/patients. Conclusion: Physiotherapists used vital signs, level of consciousness, and the IMS scale as the most prevalent assessment instruments, and the most frequently used intervention techniques were secretion removal therapy and bedside sitting. The physiotherapeutic diagnosis is still poorly established.
Functional approaches and therapeutic resources in hospital physiotherapy: a retrospective observational study
Keywords: Fisioterapia; Hospital; Qualidade; Processos de trabalho; Physiotherpy; Hospital; Quality; Work processes; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar